2014
DOI: 10.1177/1758573214536702
|View full text |Cite
|
Sign up to set email alerts
|

Racial and insurance disparities in the utilization of supportive care after inpatient admission for proximal humerus fracture

Abstract: Background: Post-discharge supportive services such as home health assistance and rehabilitation or skilled nursing facilities are often utilized after inpatient care for fracture of the proximal humerus. It is unclear whether sociodemographic disparities exist in the utilization of post-hospital supportive care. The present study aimed to evaluate the individual and combined effects of race and insurance status on the utilization of supportive services after hospital admission for fracture of the proximal hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
2
3
1
Order By: Relevance
“…While this is understandable given that these patients may require extended care in postacute care facilities depending on the severity of the adverse event, it is pertinent to stress that complications are potentially avoidable instances that can be controlled through adequate medical optimization, early mobilization, and close in-hospital observation, when needed, to allow patients to be discharged home safely and early. It is also important to mention that contrary to previous literature by Menendez and Ring, 23 we were unable to establish a racial disparity with regards to discharge destinations. It is possible that racial disparities may not exist at quality improvement hospitals.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…While this is understandable given that these patients may require extended care in postacute care facilities depending on the severity of the adverse event, it is pertinent to stress that complications are potentially avoidable instances that can be controlled through adequate medical optimization, early mobilization, and close in-hospital observation, when needed, to allow patients to be discharged home safely and early. It is also important to mention that contrary to previous literature by Menendez and Ring, 23 we were unable to establish a racial disparity with regards to discharge destinations. It is possible that racial disparities may not exist at quality improvement hospitals.…”
Section: Discussioncontrasting
confidence: 94%
“…Third, the NSQIP does not contain insurance-specific data that would have been beneficial for assessing given that previous literature has denoted significant insurance disparities present with regard to postacute care resource utilization. 23 The NSQIP also does not contain hospital-specific data, such as hospital size, location (rural/urban), and teaching status which would have been useful in adjusting for in our analysis. The database also lacks preadmission data, and therefore we were unable to account for those patients who may have previously failed nonoperative management of proximal humerus fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of lower extremity orthopaedic injury evaluation in the US EDs, Gupta et al 14 found Black patients the least likely to be admitted as inpatient. Furthermore, our findings are consistent with those of Menendez et al 15 who reported that non-Hispanic Black patients admitted with PHFs experience increased LOS compared with their White counterparts (5.1 vs. 3.7 days) in an inpatient study. 15 Our results support a persisting disparity for Black orthopaedic patients.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our findings are consistent with those of Menendez et al 15 who reported that non-Hispanic Black patients admitted with PHFs experience increased LOS compared with their White counterparts (5.1 vs. 3.7 days) in an inpatient study. 15 Our results support a persisting disparity for Black orthopaedic patients. Importantly, increased LOS has been associated with worse patient outcomes and readmission in orthopaedics.…”
Section: Discussionsupporting
confidence: 92%
“… 2 , 19 , 23 In a study of over 40,000 patients admitted to US hospitals with a proximal humerus fracture, Hispanic and Black patients were more likely to be uninsured and less likely to use post-discharge support services than White patients. 18 Two national studies assessed racial disparities in hip fracture care and showed longer time to surgery and higher rates of complications in under-represented minority patients compared with White patients. 2 , 19 …”
Section: Discussionmentioning
confidence: 99%